COMPARISON OF DIFFERENT DIAGNOSTIC GUIDELINES FOR THE DIAGNOSIS OF MACROPHAGE ACTIVATION SYNDROME COMPLICATING SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS: SINGLE CENTRE EXPERIENCE - Jelušić, Marija (Acta Clin Croat, 2018)
SUMMARY – Macrophage activation syndrome (MAS) is a potentially fatal complication of systemic juvenile idiopathic arthritis (sJIA), caused by exaggerated but ineffective immune response. The aim of the study was to compare the capacity of the HLH-2004 guidelines with the capacity of the MAS guidelines from 2005, and with the new set of classification criteria from 2016 in diagnosing MAS complicating sJIA. The study included 35 children aged 1-18 diagnosed with sJIA according to ILAR criteria and treated at the Department of Pediatrics, Division of Immunology and Rheumatology, Zagreb University Hospital Centre, in the period from 2009 to 2015. Out of 35 patients diagnosed with sJIA, there were 12 girls and 23 boys, with the mean age at disease onset (±SD) 5.51±3.65 years. Eight patients had flare of disease. With the guidelines from 2005, MAS was diagnosed in six (17.1%) patients with sJIA. With the new set of classification criteria from 2016, MAS was diagnosed in four (11.4%) patients with sJIA. MAS was not diagnosed with the HLH-2004 guidelines. In our study, four out of six patients had MAS at the onset of sJIA, and in the rest two it occurred during relapse. Two patients with MAS developed full-blown clinical picture while another four had incomplete clinical features with minor laboratory alteration. Due to the use of different diagnostic guidelines, we found difference in the prevalence of MAS. It was slightly higher in comparison to available studies, while other researched features, such as clinical characteristics, were similar.